The Use of Some Feed Additives as Growth Promoter in Broilers Nutrition - Khosravi, Ali; Boldaji, Fathollah; Dastar, Behrouz; Hasani, Saeed (International Journal of Poultry Science, 2008)
This study was undertaken to investigate the effects of some feed additives on the performance and blood parameters of broilers. In a completely randomized design, 320 1-d-old chicks were divided into four replicate groups. A control diet was prepared, based on NRC recommendations. For preparing other diets, control diet supplemented with propionic acid, protexin and nettle extract at the levels of 2, 0.1 and 1 g/kg of diet, respectively. Diet contained propionic acid resulted in significant increase in BWG during the starter and from 0-42 periods. The birds fed control diet had more FI and PI during the finisher period than those fed propionic acid. When diet supplemented with propionic acid and protexin, a significant improvement in FCR and PER was observed among this diets and other diets. Propionic acid also significantly increased HDL and decreased LDL compared to other feed additives. In conclusion, based on the results of this experiment, propionic acid and protexin can be used as a suitable alternative to antibiotic growth promoters whereas nettle extract can not.